Thermal Degradation of β-Carotene from Macauba Palm: Mathematical Modeling and Parameter Estimation - Pedro Prates Valério; Amanda Lemette Brandão; Jesus Maria Frias Celayeta; Erika Cristina Cren (International Journal of Food Studies)
Worldwide, there is a current need for new sources of vegetable oils. The natural content of total carotenoids in Acrocomia aculeata palm oil (up to 378 µg.g-1) surpasses that of many other tropical fruits, making it one of its main compositional characteristics. As far as can be verified, there is no available information on the degradation kinetics of carotenoids for A. aculeata oil, which is required to describe reaction rates and to predict changes that can occur during food processing. The present study considered prediction abilities that have emerged with the use of specific kinetic data and procedures to understand thermal processing better, as an essential unity operation. Two kinetic mechanisms were proposed to describe the overall thermal degradation of carotenoids in the oil; the first one consists of three reaction steps while the other presents only one-step reaction. Mass balance equations were numerically solved by a Backward Differentiation Formula technique. The kinetic parameters from both models were estimated through a hybrid optimisation method using the Particle Swarm Optimization and the Gauss-Newton method, followed by statistical analyses. The model with more than one reaction was shown to be overparameterized and was discarded. The model with a single reaction was highly suited to handle the experimental data available, and the dependency of its rate constant on temperature was expressed according to Arrhenius law. As far we know, this is the first time the kinetics of carotenoids thermal degradation in A. aculeata oil is investigated through modelling simulation.